Humanity autotrophy as a cosmophysical stage of planet evolution - Kaznacheev, Vlail; Trofimov, Alexander (Physics of Consciousness and Life, Cosmology and Astrophysics, 2010)
The major stage in the evolution of the Earth as a cosmophysical phenomenon is biosphere transition in autotrophic formation of Space where the reason is a new cosmophysical force, transforming possibilities of human survival and providing human output in near and far Space. The aspects of development of social organism of planet, its cosmoplanetary role and prospects of its evolution are considered.